Karakterisasi Geoteknik Lahan: Integrasi Uji Sondir (CPT) dan Laboratorium - Minmahddun, Anafi (Unmuh Babel Press, 2025)
Soil conditions are a critical factor influencing the feasibility and success of construction projects, especially for infrastructure that interacts directly with the ground, such as foundations and slopes. Geotechnical issues like excessive settlement and shallow translational landslides often occur due to insufficient understanding of soil characteristics. Soils with high clay content or low density are prone to volume changes and water saturation, which can threaten structural stability. This study aims to examine soil characteristics at the research site by integrating field tests (Cone Penetration Test/CPT) and laboratory tests to evaluate soil bearing capacity and slope instability potential. The methods included CPT at seven points and laboratory tests on seven soil samples to analyze physical and mechanical properties, such as grain distribution, Atterberg limits, and shear strength parameters. CPT results showed a dominance of silty sand with very loose to loose density in the upper layer (0–2 meters) and medium to dense density in deeper layers (>6 meters). Laboratory tests identified variations in soil classification, including silty sand (SM), silt (ML), and high-plasticity clay (CH), with low cohesion (6–10 kPa) and internal friction angle (4.85°–8.38°). Data integration revealed a high landslide risk in the upper layer due to water saturation, necessitating mitigation strategies such as deep foundations and effective drainage systems. This research provides significant contributions to safe and sustainable construction planning in areas with similar soil conditions.